Chemical constituents of Syzygium aquem (Myrtaceae) and Dysoxylum acuntangulum (Meliaceae) - Mohamad, Siti Noor Kamilah (2014)
Two plant species, Syzygium aquem and Dysoxylum acutangulum were phytochemically studied. The chemical studies on the leaves and twigs of Syzygium aquem involves extraction using three organic solvents of different polarity and isolation of compounds by using several chromatographic techniques including gravity column chromatography. The structures of the compounds were elucidated by various spectroscopic techniques including UV, IR, EIMS and NMR. Detail study on the chloroform crude extract twig and leaves of Syzygium aquem afforded three compounds where one of the compounds was identified as a chalcone, 2’,4’-dihyroxy-3’,5’-dimethyl-6’-methoxychalcone (1), obtained as orange needleshaped crystals. The other two compounds are urs-12-en-3β-ol (30) and lup-20(29)-en- 3β-ol (31). Chemical investigation on the hexane crude extract leaves and twigs of the plant have resulted a flavanone, 5-hydroxy-7-methoxy-6,8-dimethylflavanone (26), friedelin (28), and two phytosterols, stigmasterol (30) and β-sitosterol (32). A chrotacumine C (33) were isolated from root bark of Dysoxylum acutangulum.